Legal Liability Of Arbitrators And Arbitral Institutions In The Annulment Of An Arbitral Award - Najwa Fadila; Nabila Putri Aulia; Randy Harahap; Mhd Imran Pradipta (ISNU Nine-Star Multidisciplinary Journal, 2026)
The annulment of an arbitration award in Indonesia is an exceptional legal mechanism and is strictly regulated in Article 70 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (AAPS Law). Although the arbitral award is final and binding, cancellation can be made if a false document, a concealed decisive document, or a judgment born of deception is found. The submission mechanism is carried out in writing to the District Court within a period of 30 days from the registration of the decision, with supporting evidence. Arbitrators and arbitrators acquire legal immunity, but liability may arise in the event of a serious breach of the integrity of the process. This study discusses the legal basis of annulment, the form of accountability of arbitrators and arbitration institutions, the filing mechanism, and the legal consequences of annulment of an award, to provide a comprehensive understanding of legal protection and legal certainty in arbitration.